The Gold Rush of Digital Marketing: Assessing Prospects of Building Brand Awareness Overseas. Issue 1 (January 2020) - Makrides, Anna; Vrontis, Demetris; Christofi, Michael
Abstract: Advertising through digital channels—known as Digital Marketing—is recognized for its transformative impact on companies and for its immense effect on brand–consumer relationships, as it enables interactions with customers at any time and in any place. Based on these realities, this study analyzes several digital platforms and practices that have proven to be effective and assesses digital media dynamics to examine whether they can increase brand awareness on an international level. By employing a survey methodology approach with 200 respondents as a final sample, this study shows that digital marketing represents a huge potential for small- and medium-sized enterprises, giving internationalization a dominant digital attribute. Additionally, the findings reflect the noteworthy and rapid emergence of different digital marketing techniques serving different market segments. Finally, the study discusses the theoretical and managerial implications of the findings and proposes several avenues for future research.